Development and characterization of lead-free high-bismuth glazes for ornamental ceramics - Le Bescond de Coatpont, Aziliz; Caurant, Daniel; Le Bris, Lucie; Majérus, Odile; Chemmi, Atika; Wallez, Gilles (Ceramics international, 2025)
Bi2O3-based glazes were developed to replace toxic PbO-based glazes from a ternary PbO-B2O3-SiO2 reference industrial composition bearing about 70 wt % PbO for ceramic applications, with the aim of keeping very similar properties and retaining the same glazes deposition process at 840 °C. Compositions in the SiO2-B2O3-Bi2O3 system melted at 1100 °C showed a higher tendency to phase separation and crystallization than the PbO-based reference, probably due to the higher field strength of Bi3+ ion, but the addition of 5–10 mol% Al2O3 led to homogeneous glasses, even after slow cooling. The physical properties of these quaternary glasses (thermal expansion, glass transition temperature, viscosity, density, hardness, elastic modulus) were evaluated, proving comparable to those of the reference PbO-based glass. Coloring pigments (ZnAl2-xCrxO4, 0 ≤ x ≤ 2) incorporated at 840 °C in a Bi2O3-based glaze also showed similar interactions as with the PbO-based glass according to XRD-Rietveld and SEM-EDX analyses. This work leads to conclude that a quaternary SiO2-B2O3-Bi2O3-Al2O3 glass bearing about 78 wt% Bi2O3 can advantageously replace the more toxic PbO-based formulation for glazing purposes without modifying the firing process.